PENGEMBANGAN MEDIA PEMBELAJARAN TRAINER PENGAMAN ARUS BOCOR PADA INSTALASI LISTRIK RUMAH TINGGAL DI MATA KULIAH SISTEM PENGAMAN TENAGA LISTRIK - Kadek Yuda Wiryanatha, Yuda; Nyoman Santiyadnya; Wayan Mahardika Prasetya Wiratama (Universitas Pendidikan Ganesha, 2023)
This research aims to develop a learning media for leakage current safety trainers in residential electrical installations, assess its feasibility, and determine the students' response to the learning media for leakage current safety trainers in residential electrical installations in the course of power system protection. This study adopts the Research and Development (R&D) methodology. The data collection for this research is conducted through questionnaires evaluated by content experts, media experts, and students. The research results indicate that the validation test by content experts achieved a percentage of 93.1% with a qualification of highly feasible, the validation test by media experts obtained a percentage of 97.5% with a qualification of highly feasible, the small-group trial yielded a minimum score of 40 from respondents with an excellent classification, and the large-group trial also obtained a minimum score of 40 from respondents with an excellent classification. The research findings demonstrate that the learning media for leakage current safety trainers in residential electrical installations is suitable for use and has received positive responses from students in the study of power system protection in the Electrical Engineering Education Program at Undiksha University.